Governance’s Role in Business Environment of Visegrad Group / Maghreb Countries - Sofian Bouhlel (European Scientific Journal, ESJ, 2022)
This paper focuses on identifying, conceptualizing, and explaining good governance in Visegrád Group (Czech Republic, Hungary, Poland and Slovakia) and Maghreb countries (Algeria, Libya, Mauritania, Morocco and Tunisia). In addition, the research is an attempt to investigate the relationship between the good governance and the business environment in these zones by creating a Pearson correlation between the six indicators of good governance and the score of ease of doing business. This research aims to examine the importance of the indicators of rule of law, political stability, control of corruption, voice and accountability, regulatory quality, and government effectiveness to implement an attractive business environment in these two regions using a regression analysis. The empirical data were collected from the Worldwide Governance Indicators (WGI) (1996–2020) and Doing Business Report (2015 – 2020), World Bank. This paper represent an argument for the relevance of governance indicators on the business environment which was justified by a strong correlation near to 1 for all the indicators. As a general perception, an attractive business environment will be one of the most important results of the existence of good governance. The second objective is to prove the relevance of governance quality for the ease of doing business in order to achieve the development for both regions.